Tourism, Governance and Economic Growth in India - MISHRA, P. K.; ROUT, Himanshu B.; CHAINI, S. R. (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).21, 2021)
This research work studied the relationship between tourism, governance quality and economic growth in India. It has been argued that the contribution of tourism sector expansion to the real economic growth significantly depends on the quality of governance that is prevalent in the country. The study empirically supports the existence of tourism-led growth hypothesis in Indian context while business confidence, economic freedom and regulatory quality have positive influences, and government effectiveness and corruption control have negative impacts on the economic growth over the sample period. Therefore, the study recommends for promoting polices which ensure business confidence, economic freedom and regulatory quality in the country. It is also suggested that the policies which ensure government effectiveness and control corruption be revisited, reframed, if required, and implemented more stringently along with the polices for effective monitoring and assessment.